VARIASI PENAMBAHAN SUKROSA TERHADAP MUTU COCOGHURT MENGGUNAKAN Enterococcus faecalis UP-11 YANG DIISOLASI DARI TEMPOYAK - Ade Syaputra; Usman Pato; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Cocoghurt is one type of functional food derived from fermentation of coconut milk by probiotic bacteria. The aim of the research was to evaluate the effect of sugar on the quality of cocoghurt. A  Completely  Randomized Design  (CRD)  was  used  in  the  research  with  four  treatments  and  four replications. Treatment consisted of SK1 (0%) sucrose (w/v ), SK2 (6%) sucrose (w/v), SK3 (12%) sucrose (w/v),  SK4 (18%) sucrose (w/v). Data obtained were treated by the Analysis of Variance followed by Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. The results show that the addition of various sucrose significantly effected the degree of acidity (pH), total solid, fat content, but had no significant effect on the total lactid acid, total lactic acid bacteria, protein and ash contents. Addition of sucrose did not influence the major quality parameter of cocoghurt (total lactic acid bacteria).     Keywords: Sucrose, Cocoghurt, Enterococcus faecalis, Tempoyak